2016
DOI: 10.1016/j.bjid.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Pain prevalence, characteristics and associated factors in human T-cell lymphotropic virus type 1 infected patients: a systematic review of the literature

Abstract: Pain is a common complaint in human T-cell lymphotropic virus type 1 infected patients, with lower back pain as the most frequent site. Pain can either be nociceptive, neuropathic, or both, is frequently severe, and negatively affects quality of life. Only studies of two countries were included in this review, limiting the external validity of the conclusions. The heterogeneity of variables prevented us from implementing a meta-analysis. Further research should better characterize the pain and explore its impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
12
1
2
Order By: Relevance
“…As reviewed in 2016, pain prevalence among HTLV-1 infected individuals varies from 35–88% and is more commonly reported as persistent [ 46 ]. However, pain/discomfort, despite affecting ~85% of patients with HAM/TSP was not the most affected domain, with mobility and usual activities even more frequently reported.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed in 2016, pain prevalence among HTLV-1 infected individuals varies from 35–88% and is more commonly reported as persistent [ 46 ]. However, pain/discomfort, despite affecting ~85% of patients with HAM/TSP was not the most affected domain, with mobility and usual activities even more frequently reported.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the tDCS analgesic effects are somewhat less marked for patients with neuropathic pain, consistent with the guideline published by Lefaucheur et al 60 We did not classify HTLV-related pain 105 as purely neuropathic, as those patients generally suffer from a mixture of nociceptive (low back) and neuropathic pain (lower limbs), and many of them have diffuse pain. 95 Consequently, we included only 4 neuropathic pain studies, 8,41,54,104 and only one of them 54 showed a >30% reduction in pain intensity (Tables 1 and 2). This study involved 40 participants with diabetic polyneuropathy and showed a decrease in pain intensity and increase in pressure pain thresholds after consecutive sessions, but not at 1-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…39,88,92,93,112 The most frequent pain syndromes are osteoarthritis-related pain, low back pain (LBP), headaches, and neuropathic pain syndromes. 2,5,39,40,92,93,95 For instance, the lifetime prevalence of acute LBP is close to 70%, and it has been suggested that more than half will eventually experience chronification, 12,47 ranking chronic LBP as the first cause of years lived with disability 80,114 worldwide. Chronic pain has known associations with depressed mood, fatigue, and catastrophizing thoughts.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal tuberculosis may induce varying degrees of damage to the spinal cord nerve roots ( 40 ), resulting in neuropathic pain. A clinical study revealed that a third of patients with rheumatoid arthritis have symptoms of neuropathic pain ( 41 ), and a review reported that approximately 53.1% of HTLV-1 carriers have symptoms of neuropathic pain ( 42 ). The conventional MAPKs include the p38 isoforms, extracellular signal-regulated kinases 1/2 (ERK1/2) and JNKs ( 43 ).…”
Section: Discussionmentioning
confidence: 99%